2010
DOI: 10.1073/pnas.1002506107
|View full text |Cite
|
Sign up to set email alerts
|

Learning-dependent plasticity with and without training in the human brain

Abstract: Long-term experience through development and evolution and shorter-term training in adulthood have both been suggested to contribute to the optimization of visual functions that mediate our ability to interpret complex scenes. However, the brain plasticity mechanisms that mediate the detection of objects in cluttered scenes remain largely unknown. Here, we combine behavioral and functional MRI (fMRI) measurements to investigate the human-brain mechanisms that mediate our ability to learn statistical regulariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…This interpretation is consistent with a previous study that found that classically trained musicians process pitch in a facilitated manner (Jäncke, 2009). Our findings suggest that music training modulates the exposure type of perceptual learning (Zhang & Kourtzi, 2010) for pitch. This skill could explain why musicians can generalize their auditory skills (i.e., pitch processing) beyond musically relevant tasks, such as discriminating pitch violations in foreign language prosody (Marques et al, 2007).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This interpretation is consistent with a previous study that found that classically trained musicians process pitch in a facilitated manner (Jäncke, 2009). Our findings suggest that music training modulates the exposure type of perceptual learning (Zhang & Kourtzi, 2010) for pitch. This skill could explain why musicians can generalize their auditory skills (i.e., pitch processing) beyond musically relevant tasks, such as discriminating pitch violations in foreign language prosody (Marques et al, 2007).…”
Section: Discussionmentioning
confidence: 77%
“…Two mechanisms of perceptual learning have been proposed: the feedback-guided attentional process is believed to lead to feature-dependent learning, while passive exposure to stimuli is hypothesized to lead to learning that can be generalized to untrained features (Zhang & Kourtzi, 2010). For example, learning to discriminate pitch contours in melodies could be generalized to the discrimination of linguistic pitch contours (i.e., prosody; Marques, Moreno, Castro, & Besson, 2007).…”
mentioning
confidence: 99%
“…In the meantime, the abundance and composition of AOA stayed largely unchanged (Figures 2 and 4). The increasing lines of evidence suggest that AOB are favored in high ammonium environment, while AOA may play an important role in ammonium-poor environment (Gubry-Rangin et al, 2010; Zhang et al, 2010). However, there is also evidence that AOA pure culture may grow at the concentration up to 15 mM ammonium (Tourna et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This number of voxels is similar to that used in previous MVPA studies of functionally defined ROIs (Zhang, Kriegeskorte, Carlin, & Rowe, 2013;Zhang & Kourtzi, 2010;Haynes & Rees, 2005). In six cases (two occurrences each in three participants), fewer than 120 voxels were found in an ROI after registration from group level to individual images when excluding brain edge voxels, so slightly smaller ROIs were used (range = 77-114 voxels).…”
Section: Roi Definitionmentioning
confidence: 95%